Health Profile of Broiler Chickens using a Ratio of Rice Husk, Sawdust and Lime as Litter - Asminaya, Nur Santy (Jambura Journal of Animal Science, 2024)
This study aims to determine the effect of the ratio of rice husk, sawdust, and lime as litter on the health of broilers. This study used a completely randomized design (CRD) with five treatments and four replications. Each replication consisted of five broilers. The treatment given included P1 = 100% rice husk. P2 = 100% sawdust, P3 = 70% rice husk, 25% sawdust, and 5% lime. P4 = 25% rice husk, 70% sawdust, 5% lime. P5 = 47.5% rice husk, 47.5% sawdust, and 5% lime. The research parameters included: physical characteristics of external and internal organs, percentage of internal organ weight, and broiler mortality. This study's results indicate abnormal physical characteristics of broilers' external organs (legs, feathers, and cloaca) and internal organs (liver, spleen, thymus, and kidneys). The average percentage of liver, heart, and gizzard weight of broilers in this study ranged from 3.98-357%, 0.70-0.84%, and 3.29-4.0%. The average mortality rate reached 0.01% of 100 broilers reared for six weeks. It was concluded that the rice husk, sawdust, and lime ratio showed abnormal physical characteristics in broilers' external and internal organs. However, it did not significantly affect (P0.05) the percentage of internal organ weight and broiler mortality